Relation between gastric histology and gastric juice pH and nitrite and N-nitroso compound concentrations in the stomach after surgery for duodenal ulcer. Issue 5 (May 1984) - Watt, P C; Sloan, J M; Donaldson, J; Campbell, G; Kennedy, T L
Abstract : Formation of N-nitroso compounds in gastric juice has been implicated in the pathogenesis of cancer in the stomach after operation. Gastric juice was aspirated from 85 subjects: 23 were controls, 51 had previously undergone vagotomy and gastrojejunostomy, and 11 had previously undergone vagotomy and pyloroplasty. The gastric juice samples were analysed for pH, nitrite, and total N-nitroso compounds. A significant correlation was found between pH and nitrite concentration (p less than 0.01). No significant correlation was found between pH and total N-nitroso compound concentration or between nitrite and N-nitroso compound concentration. The vagotomy and gastrojejunostomy patients had higher pH values and higher concentrations of nitrites and N-nitroso compounds than controls (p = 0.01 in all cases). The 51 vagotomy and gastrojejunostomy patients also underwent endoscopy and biopsy. They were divided into three groups: group 1 (21 patients) had no intestinal metaplasia and no more than mild dysplasia; group 2 (20 patients) had intestinal metaplasia; and group 3 (10 patients) had moderate or severe dysplasia. Groups 2 and 3 both had higher pH values and higher nitrite concentrations than group 1 (p = 0.01 in all cases). There was no significant difference, however, between either group 2 or 3 and group 1 for total N-nitroso compound concentration. Since there was no simple linear relation between pH and N-nitroso compound concentration, it was concluded that formation of N-nitroso compounds at high pH was unlikely to be involved in the pathogenesis of gastric cancer in the hypochlorhydric stomach after operation. The relation between nitrite and histological abnormality was not associated with a similar relation between N-nitroso compounds and histological abnormality. It therefore appears that there is no simple relation between N-nitroso compounds and the pathogenesis of premalignant gastric mucosal changes.